Fracture mechanics analysis of cracking in plain and reinforced concrete using the boundary element method - Aliabadi, MH; Saleh, Abdul Latif (Elsevier Science, 2002)
Boundary element formulations for modelling the nonlinear behaviour of concrete are reviewed. The analysis based on the dual boundary element method (BEM) to represent the cracks in concrete is presented. The fictitious crack is adopted to represent the fracture process zone in concrete. The influence of reinforcements on the concrete is considered as a distribution of forces over the region of attachment. The yielding of reinforcement is considered when the total force at any section of the reinforcement is greater than the yielding force and is assumed to be broken when the strain reaches the maximum strain. In using the BEM to simulate cracks, the crack path need not be known in advance since it can be calculated during the iteration process and as such remeshing becomes obsolete. The numerical results obtained are compared to the FEM analysis.